The Chemical characteristic of Moringa leaf snack (Moringa oleifera) as a functional food to prevent stunting: Karakteristik Kimia Kudapan Daun Kelor (Moringa oleifera) sebagai Pangan Fungsional Pencegah Stunting - Hesty Widowati; Rahmah Utami Budiandari; SMF Hanum; Krisjayanti Sukarno (Universitas Muhammadiyah Sidoarjo, 2023)
Stunting is malnutrition related to nutritional insufficiency in the past so that nutritional problems are chronic. The prevalence of stunting in Indonesia is higher than other ASEAN countries, ranking fifth in the world. Functional food can be used as an alternative in preventing toddler stunting, one of which is by adding Moringa leaves to the snacks that toddlers like, namely sempol and pudding. The purpose of this study was to determine the chemical characteristics of moringa leaf-based snacks, namely sempol and pudding. The study uses a nested design with two factors. The first factor is the type of preparations, namely sempol and pudding, while the second factor is the concentration of the addition of Moringa leaves, namely 5%, 10% and 15%. Data were analyzed using ANOVA and minitab. The research results showed no significant effect on the values of water content, ash content, protein and fat content in sempol and moringa pudding. Based on the test results, the water content of sempol with moringa 15% is 54%, with an ash content of 2.11%, a fat content of 1.56% and a protein content of 36.58%. Meanwhile, 15% Moringa pudding has a moisture content of 77.5%, ash content of 0.36%, fat content of 5.97%, and protein content of 17.26%. Highlights: Prevalence of Stunting: Stunting is a critical malnutrition issue, especially in Indonesia, ranking fifth globally among ASEAN countries, highlighting the urgent need for effective interventions. Functional Food Approach: Incorporating Moringa leaves into popular toddler snacks (sempol and pudding) offers a potential solution to combat stunting through improved nutritional value and dietary diversity. Chemical Characteristics Study: The research examines the impact of Moringa leaf concentration (5%, 10%, 15%) on water, ash, protein, and fat content in both snacks, providing valuable insights into their nutritional profiles. Keywords : Stunting, functional food, Moringa leaf snacks